Nearsurface buckling in laminate composite material with imperfect interlayer contact - Bystrov, V.M.; Dekret, V.A.; Zelenskiy, V.S. (Reports of the National Academy of Sciences of Ukraine, 2022)
Using the basic relations of the three-dimensional linearized theory of stability within the model of a piecewisehomogeneous medium, a solution is obtained for the problem of stability of a layered composite material under compression by a surface load along the reinforcement direction. The case of imperfect contact between layers is considered, which is modeled by a periodic system of macrocracks in the form of a mathematical section for the stress-free crack surfaces. A calculation model is used for the boundary conditions on the sides of a multilayer sample made of a composite material that meet the symmetry conditions. The influence of the crack size on the damping of near-surface buckling modes and critical loads is studied. For the numerical solution of the problem, the grid method based on a modified variational-difference approach was used. Within the framework of the computational experiment, serial and parallel algorithms of the Cholesky methods and subspace iteration were applied.